The Palm-Up Puzzle: Meanings and Origins of a Widespread Form in Gesture and Sign - Cooperrider, Kensy; Abner, Natasha; Goldin-Meadow, Susan (Frontiers in Communication, 2018)
During communication, speakers commonly rotate their forearms so that their palms turn upward. Yet despite more than a century of observations of such palm-up gestures, their meanings and origins have proven difficult to pin down. We distinguish two gestures within the palm-up form family: the palm-up presentational and the palm-up epistemic. The latter is a term we introduce to refer to a variant of the palm-up that prototypically involves lateral separation of the hands. This gesture—our focus—is used in speaking communities around the world to express a recurring set of epistemic meanings, several of which seem quite distinct. More striking, a similar palm-up form is used to express the same set of meanings in many established sign languages and in emerging sign systems. Such observations present a two-part puzzle: the first part is how this set of seemingly distinct meanings for the palm-up epistemic are related, if indeed they are; the second is why the palm-up form is so widely used to express just this set of meanings. We propose a network connecting the different attested meanings of the palm-up epistemic, with a kernel meaning of absence of knowledge, and discuss how this proposal could be evaluated through additional developmental, corpus-based, and experimental research. We then assess two contrasting accounts of the connection between the palm-up form and this proposed meaning network, and consider implications for our understanding of the palm-up form family more generally. By addressing the palm-up puzzle, we aim, not only to illuminate a widespread form found in gesture and sign, but also to provide insights into fundamental questions about visual-bodily communication: where communicative forms come from, how they take on new meanings, and how they become integrated into language in signing communities.